2016
DOI: 10.1186/s12913-016-1385-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-creation of an ICT-supported cancer rehabilitation application for resected lung cancer survivors: design and evaluation

Abstract: BackgroundLung cancer (LC) patients experience high symptom burden and significant decline of physical fitness and quality of life following lung resection. Good quality of survivorship care post-surgery is essential to optimize recovery and prevent unscheduled healthcare use. The use of Information and Communication Technology (ICT) can improve post-surgery care, as it enables frequent monitoring of health status in daily life, provides timely and personalized feedback to patients and professionals, and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
120
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(126 citation statements)
references
References 43 publications
(50 reference statements)
2
120
0
Order By: Relevance
“…A few studies investigated patient preferences for use of ICT in (rehabilitation) health care using a qualitative research design [7,24,25]. Therefore, frequency data found in the current study could not be compared to other literature.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A few studies investigated patient preferences for use of ICT in (rehabilitation) health care using a qualitative research design [7,24,25]. Therefore, frequency data found in the current study could not be compared to other literature.…”
Section: Discussionmentioning
confidence: 97%
“…Examples of e-Health in rehabilitation include virtual reality, computer games, assistive technology and online communication tools. Especially, long-term medical care needs could be addressed at significant lower expenditures [5], by means of improved accessibility to rehabilitation programs for clients with mobility impairments [6][7][8], expanded continuity of care and increased self-management by promoting personalized care, choice and personal autonomy [9]. Indeed, a number of studies showed that e-health is acceptable for subgroup of patients in rehabilitation care [9][10][11] and has the potential to support management of chronic conditions such as Alzheimer's/ dementia [12], diabetes [13,14] and COPD [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations